DEVELOPMENT OF CHARACTER VALUE-BASED EDUCATION GAMES FOR ELEMENTARY SCHOOL (SD) STUDENTS - Yulianti, Yulianti; Rahayu, Marta Indah; Sulistyowati, Prihatin (Faculty of Education Universitas Negeri Malang, 2022)
This study aims to determine the feasibility, practicality and effectiveness of the educational game